The impact of the COVID-19 pandemic on the poor: Insights from the Hrishipara diaries - Risto Rönkkö; Stuart Rutherford; Kunal Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
In this paper, we examine the economic impact of the COVID-19 pandemic on the livelihoods of the poor. We use an unusually rich data set from a 'financial diaries' study known as the Hrishipara Daily Diaries Project. The data set tracks the economic and financial transactions of 60 individuals and their families in a semi-rural setting in Bangladesh on a real-time basis from October 2019 to September 2020. We document individual diarists' behavioural responses to COVID-19, which reveal the varied experiences of the poor during the pandemic. We find that the pandemic and associated government lockdowns had significant negative effects on the livelihoods of the poor in our study, with financial inflows and outflows, incomes, and household expenditures below pre-pandemic levels during the pandemic period. To cope with the pandemic, households drew down on their cash reserves at home, as well as cutting down on non-food expenditures to protect their spending on food.
Keywords: B40; I15; I32; O12; 330; COVID-19 pandemic; lockdowns; diaries; livelihoods; Bangladesh